Key concepts in cultural theory (Routledge, 2004)
Here is an up-to-date and comprehensive survey of over 350 of the key terms encountered in cultural theory today. Each entry provides clear and succinct explanations for students throughout a wide range of disciplines. Topics include: Deconstruction Epistemology Feminism Hermene utics Holism Methodology Postmodernism Semiotics Soc iobiology Major entries are accompanied by suggestions for further reading, and there is also a bibliography of essential texts in cultural theory.